Pharyngeal biorhythms during oral milk challenge in high‐risk infants: Do they predict chronic tube feeding?. Issue 2 (13th November 2022) - Hasenstab, Kathryn A.; Prabhakar, Varsha; Helmick, Roseanna; Yildiz, Vedat; Jadcherla, Sudarshan R.
Abstract: Background: Eating difficulties are common in high‐risk neonatal intensive care unit (NICU) infants; mechanisms remain unclear. Crib‐side pharyngo‐esophageal motility testing is utilized to assess contiguous swallowing physiology, and cross‐system interplay with cardio‐respiratory rhythms. Aims were to: (1) identify whether distinct pharyngeal rhythms exist during oral milk challenge (OMC), and (2) develop a chronic tube feeding risk prediction model in high‐risk infants. Methods: Symptomatic NICU infants ( N  = 56, 29.7 ± 3.7 weeks birth gestation) underwent pharyngo‐esophageal manometry with OMC at 40.9 ± 2.5 weeks postmenstrual age (PMA). Exploratory cluster data analysis (partitioning around k‐medoids) was performed to identify patient groups using pharyngeal contractile rhythm data (solitary swallows and swallows within bursts). Subsequently, (a) pharyngeal‐esophageal, cardio‐respiratory, and eating method characteristics were compared among patient groups using linear mixed models, and (b) chronic tube feeding prediction model was created using linear regression. Results: Three distinct patient groups were identified with validity score of 0.6, and termed sparse (high frequency of solitary swallows), intermediate, or robust (high swallow rate within bursts). Robust group infants had: lesser pharyngeal and esophageal variability, greater deglutition apnea, pharyngeal activity, and esophageal activity (all p  < 0.05), but less frequent heart rate decreases ( p  < 0.05) with improved clinical outcomes (milk transfer rate, p  < 0.001, and independent oral feeding at discharge, p  < 0.03). Chronic tube feeding risk = −11.37 + (0.22 × PMA) + (−0.73 × bronchopulmonary dysplasia) + (1.46 × intermediate group) + (2.57 × sparse group). Conclusions: Robust pharyngeal rhythm may be an ideal neurosensorimotor biomarker of independent oral feeding. Differential maturation of cranial nerve‐mediated excitatory and inhibitory components involving foregut, airway, and cardiac rhythms distinguishes the physiologic and pathophysiologic basis of swallowing and cardio‐respiratory adaptation. Abstract : Exploratory analysis of pharyngeal swallowing rhythms during bottle feeding challenge in high‐risk neonates revealed three distinct patient groups: (A) Sparse—primarily solitary swallows, (B) Intermediate—solitary swallows and shorter bursts, and (C) Robust—primarily longer bursts. Patient group and postmaturational age predict independent oral feeding success.